Restoring of miR-193a-5p Sensitizes Breast Cancer Cells to Paclitaxel through P53 Pathway - Monireh Khordadmehr; Roya Shahbazi; Behzad Baradaran; Sanam Sadreddini; Dariush Shanebandi; Khalil Hajiasgharzadeh (Tabriz University of Medical Sciences, 2020)
Purpose: Recent evidence presented the important role of microRNAs in health and disease particularly in human cancers. Among those, miR-193 family contributes as a tumor suppressor in different benign and malignant cancers like breast cancer (BC) via interaction with specific targets. On the other hand, it was stated that miR-193 is able to modulate some targets in chemoresistant cancer cells. Therefore, the aim of this study was to evaluate the potential function of miR-193a-5p and paclitaxel in the apoptosis induction by targeting P53 in BC cells. Methods: At first, miR-193a-5p mimics were transfected to MDA-MB-231 BC cell line which indicated the lower expression level of miR-193a-5p. Subsequently, the transfected cells were treated with paclitaxel. Then, cell viability, apoptosis, and migration were evaluated by MTT, flow cytometry and DAPI staining, and scratch-wound motility assays, respectively. Moreover, the expression levels of P53 was evaluated by qRT-PCR. Results: The expression level of miR-193a-5p was restored in MDA-MB-231 cells which profoundly inhibited the proliferation (P<0.0001), induced apoptosis (P<0.0001) and harnessed migration (P<0.0001) in the BC cells and more effectiveness was observed in combination with paclitaxel. Interestingly, increased miR-193a-5p expression led to a reduction in P53 mRNA, offering that it can be a potential target of miR-193a. Conclusion: Taken together, it is concluded that the combination of miR-193a-5p restoration and paclitaxel could be potentially considered as an effective therapeutic strategy to get over chemoresistance during paclitaxel chemotherapy